Efficacy of Oral Progesterone Treatment in Women with Unexplained Recurrent First Miscarriages: Oral Progesterone Treatment in Women with Unexplained Recurrent First Miscarriages - Aziz, Misbah Ul Ain; Zainab, Sadia (Pakistan Journal of Health Sciences, 2026)
Recurrent miscarriage in the first trimester is a difficult and emotionally draining problem, affecting nearly 1–2% of women. In many cases, no clear cause can be found. Progesterone is known to help support early pregnancy by stabilizing the endometrium and reducing uterine contractions. Objective: To assess how effective oral progesterone is in women who have had repeated unexplained first-trimester miscarriages. Methods: This was a prospective, non-randomized single-arm interventional study conducted in the Department of Obstetrics and Gynecology, Combined Military Hospital, Bahawalpur, between August 02, 2024, and February 01, 2025. A total of 152 women aged 20–40 years, each with a history of ≥2 unexplained consecutive first-trimester miscarriages and a confirmed intrauterine viable pregnancy of <12 weeks, were included. All participants received oral dydrogesterone (10 mg twice daily) until completion of 12 weeks’ gestation, with follow-up assessments every two weeks. Data were analyzed using SPSS version 26.0. Efficacy was defined as pregnancy continuation beyond 12 completed weeks of gestation following therapy; live birth (where available) was recorded as an additional outcome. Associations were examined using chi-square tests and multivariable binary logistic regression, with p<0.05 considered statistically significant. Conclusions: In this single-arm cohort, oral dydrogesterone was associated with continuation of pregnancy beyond 12 weeks or live birth in 78.9% of women with unexplained recurrent first-trimester miscarriages. As no untreated comparator group was included, this study cannot determine whether dydrogesterone improves live birth outcomes compared with no progesterone therapy; randomized controlled studies are needed to confirm comparative effectiveness.